Sex-specific growth in chicks of the sexually dimorphic Black-tailed Godwit - Loonstra, A. H. Jelle; Verhoeven, Mo A.; Piersma, Theunis (Ibis, 2018)
Sexual size dimorphism (SSD) is common in birds and has been linked to various selective forces. Nevertheless, the question of how and when the sexes start to differentiate from each other is poorly studied. This is a critical knowledge gap, as sex differences in growth may cause different responses to similar ecological conditions. In this study, we describe the sex-specific growth - based on body mass and five morphometric measurements - of 56 captive Black-tailed Godwit Limosa limosa limosa chicks raised under adlibitum food conditions, and conclude that all six growth curves are sex-specific. Females are the larger sex in terms of body mass and skeletal body size. To test whether sex-specific growth leads to sex-specific susceptibility to environmental conditions, we compared the age-specific sizes of male and female chicks in the wild with those of Black-tailed Godwits reared in captivity. We then tested for a relationship between residual growth and relative hatching date, age, sex and habitat type in which the wild chicks were born. Early-hatched chicks were relatively bigger and in better condition than late-hatched chicks, but body condition and size were not affected by natal habitat type. Female chicks deviated more negatively from the sex-specific growth curves than male chicks for body mass and total-head length. This suggests that the growth of the larger females is more susceptible to limiting environmental conditions. On average, the deviations of wild chicks from the predicted growth curves were negative for all measurements, which suggests that conditions are limiting in the current agricultural landscape. We argue that in estimating growth curves for sexually dimorphic species, it is critical first to make accurate sex and age determinations.